Difference between revisions of "Passing to the quotient (function)"

From Maths
Jump to: navigation, search
(Created page with "==Definition== Given a function, {{M|f:X\rightarrow Y}} and another function, {{M|w:X\rightarrow W}} (I have chosen {{M|W}} to mean "whatever") we can say: : '''{{M|f}} may be...")
 
m (Made the diagram a bit neater, added in some points to make it easier to remember)
Line 3: Line 3:
 
: '''{{M|f}} may be factored through {{M|w}}'''
 
: '''{{M|f}} may be factored through {{M|w}}'''
 
if {{M|f}} and {{M|w}} are such that:
 
if {{M|f}} and {{M|w}} are such that:
* <math>\forall x,y\in X[w(x)=w(y)\implies f(x)=f(y)]</math> (this is the same as: <math>\forall x,y\in X[f(x)\ne f(y)\implies w(x)\ne w(y)]</math>)
+
* <math>\forall x,y\in X[w(x)=w(y)\implies f(x)=f(y)]</math>  
 +
*: (this is the same as: <math>\forall x,y\in X[f(x)\ne f(y)\implies w(x)\ne w(y)]</math>)
 
Then {{M|f}} ''induces'' a function, {{M|\tilde{f} }} such that <math>f=\tilde{f}\circ w</math>, or more simply that the following [[Commutative diagram|diagram commutes]]:
 
Then {{M|f}} ''induces'' a function, {{M|\tilde{f} }} such that <math>f=\tilde{f}\circ w</math>, or more simply that the following [[Commutative diagram|diagram commutes]]:
:: <math>
+
{| class="wikitable" border="1"
 +
|-
 +
| style="font-size:1.5em;" | <math>
 
\begin{xy}
 
\begin{xy}
 
\xymatrix{
 
\xymatrix{
Line 13: Line 16:
 
\end{xy}
 
\end{xy}
 
</math>
 
</math>
 +
|-
 +
! Diagram
 +
|}
 
Note:
 
Note:
 
# {{M|\tilde{f} }} may be explicitly written as {{M|\tilde{f}:W\rightarrow Y}} by {{M|\tilde{f}:v\mapsto f(w^{-1}(v))}}
 
# {{M|\tilde{f} }} may be explicitly written as {{M|\tilde{f}:W\rightarrow Y}} by {{M|\tilde{f}:v\mapsto f(w^{-1}(v))}}
 +
#* Or indeed {{M|1=\tilde{f}:=f\circ w^{-1} }}
 +
#* This is actually an abuse of notation as {{M|w^{-1}(x\in W)}} is a subset of {{M|X}}, however it is safe to use it because (as is proved below) {{M|f}} of any element of {{M|w^{-1}(x\in W)}} for a given {{M|x}} is the same.
 
# The function {{M|\tilde{f} }} is unique if {{M|w}} is [[Surjection|surjective]]
 
# The function {{M|\tilde{f} }} is unique if {{M|w}} is [[Surjection|surjective]]
 +
===Points to remember===
 +
* Remembering the requirements:
 +
*: We want to induce a function {{M|\tilde{f}:W\rightarrow Y}} - if {{M|1=w(x)=w(y)}} then {{M|1=\tilde{f}(w(x))=\tilde{f}(w(y))}} just by composition.
 +
*: If {{M|1=f(x)\ne f(y)}} we're screwed in this case. So it is easy to see that we must have {{M|1=[w(x)=w(y)]\implies[f(x)=f(y)]}} otherwise we cannot proceed.
 
==Proof of claims==
 
==Proof of claims==
 
{{Begin Theorem}}
 
{{Begin Theorem}}
Line 57: Line 69:
 
{{End Proof}}
 
{{End Proof}}
 
{{End Theorem}}
 
{{End Theorem}}
 
 
==References==
 
==References==
 
<references/>
 
<references/>
 
 
{{Definition|Abstract Algebra}}
 
{{Definition|Abstract Algebra}}

Revision as of 00:19, 19 November 2015

Definition

Given a function, [ilmath]f:X\rightarrow Y[/ilmath] and another function, [ilmath]w:X\rightarrow W[/ilmath] (I have chosen [ilmath]W[/ilmath] to mean "whatever") we can say:

[ilmath]f[/ilmath] may be factored through [ilmath]w[/ilmath]

if [ilmath]f[/ilmath] and [ilmath]w[/ilmath] are such that:

  • [math]\forall x,y\in X[w(x)=w(y)\implies f(x)=f(y)][/math]
    (this is the same as: [math]\forall x,y\in X[f(x)\ne f(y)\implies w(x)\ne w(y)][/math])

Then [ilmath]f[/ilmath] induces a function, [ilmath]\tilde{f} [/ilmath] such that [math]f=\tilde{f}\circ w[/math], or more simply that the following diagram commutes:

[math] \begin{xy} \xymatrix{ X \ar[r]^w \ar[dr]_f & W \ar@{.>}[d]^{\tilde{f}}\\ & Y } \end{xy} [/math]
Diagram

Note:

  1. [ilmath]\tilde{f} [/ilmath] may be explicitly written as [ilmath]\tilde{f}:W\rightarrow Y[/ilmath] by [ilmath]\tilde{f}:v\mapsto f(w^{-1}(v))[/ilmath]
    • Or indeed [ilmath]\tilde{f}:=f\circ w^{-1}[/ilmath]
    • This is actually an abuse of notation as [ilmath]w^{-1}(x\in W)[/ilmath] is a subset of [ilmath]X[/ilmath], however it is safe to use it because (as is proved below) [ilmath]f[/ilmath] of any element of [ilmath]w^{-1}(x\in W)[/ilmath] for a given [ilmath]x[/ilmath] is the same.
  2. The function [ilmath]\tilde{f} [/ilmath] is unique if [ilmath]w[/ilmath] is surjective

Points to remember

  • Remembering the requirements:
    We want to induce a function [ilmath]\tilde{f}:W\rightarrow Y[/ilmath] - if [ilmath]w(x)=w(y)[/ilmath] then [ilmath]\tilde{f}(w(x))=\tilde{f}(w(y))[/ilmath] just by composition.
    If [ilmath]f(x)\ne f(y)[/ilmath] we're screwed in this case. So it is easy to see that we must have [ilmath][w(x)=w(y)]\implies[f(x)=f(y)][/ilmath] otherwise we cannot proceed.

Proof of claims

Claim: the induced function, [ilmath]\tilde{f} [/ilmath] exists and is given unambiguously by [ilmath]\tilde{f}:v\mapsto f(w^{-1}(v))[/ilmath]


Existence

Let [ilmath]\tilde{f}:W\rightarrow Y[/ilmath] be given by: [ilmath]f:v\mapsto f(w^{-1}(v))[/ilmath] - I need to prove this is a Function
This means I must check it is well defined, a function must associate each point in its domain with exactly 1 element of its codomain
Let [ilmath]v\in W[/ilmath] be given
Let [ilmath]a\in w^{-1}(v)[/ilmath] be given
Let [ilmath]b\in w^{-1}(v)[/ilmath] be given
We know [math]\forall a\in w^{-1}(v)[/math] that [math]w(a)=v[/math] by definition of [math]w^{-1}[/math]
This means [math]w(a)=w(b)[/math]
But by hypothesis [math]w(a)=w(b)\implies f(a)=f(b)[/math]
So [math]f(a)=f(b)[/math]
Thus given an [ilmath]a\in w^{-1}(v)[/ilmath], [math]\forall b\in w^{-1}[f(a)=f(b)][/math]
We now know (formally) that: (given a [ilmath]v[/ilmath]) [math]\exists y\in Y\forall a\in w^{-1}(v)[f(a)=y][/math] - notice the [math]\exists y[/math] comes first. We can uniquely define [math]f(w^{-1}(v))[/math]
Since [ilmath]v\in W[/ilmath] was arbitrary we know [math]\forall v\in W\exists y\in Y\forall a\in w^{-1}(v)[f(a)=y][/math]
We have now shown that [math]\tilde{f}[/math] can be well defined (as the function that maps a [ilmath]v\in W[/ilmath] to a [ilmath]y\in Y[/ilmath].
To calculate [math]\tilde{f}(v)[/math] we may choose any [math]a\in w^{-1}(v)[/math] and define [math]\tilde{f}(v)=f(a)[/math] - we know [math]f(a)[/math] is the same for whichever [math]a\in w^{-1}(v)[/math] we choose.
So we know the function [math]\tilde{f}:W\rightarrow Y[/math] given by [math]\tilde{f}:x\mapsto f(w^{-1}(x))[/math] exists


This completes the proof[1]

Claim: if [ilmath]w[/ilmath] is surjective then the induced [ilmath]\tilde{f} [/ilmath] is unique


Uniqueness

Suppose another function exists, [math]\tilde{f}':W\rightarrow Y[/math] that isn't the same as [math]\tilde{f}:W\rightarrow Y[/math]
That means [math]\exists u\in W:[\tilde{f}(u)\ne\tilde{f}'(u)][/math] (and as [ilmath]w[/ilmath] is surjective [ilmath]\exists x\in X[p(x)=u][/ilmath])
Both [ilmath]\tilde{f} [/ilmath] and [ilmath]\tilde{f}'[/ilmath] have the property of [math]f=\tilde{f}\circ w=\tilde{f}'\circ w[/math] so:
by hypothesis, for all [ilmath]x[/ilmath] however, we know [ilmath]\tilde{f} [/ilmath] and [ilmath]\tilde{f}'[/ilmath] don't agree over their entire domain, the [ilmath]p(x)[/ilmath] they do not agree on violate this property (as [ilmath]f[/ilmath] cannot be two things for a given [ilmath]x[/ilmath])
This contradicts that [ilmath]\tilde{f} [/ilmath] and [ilmath]\tilde{f}'[/ilmath] are different


This completes the proof[1]

Notes:
  1. Notice that if [ilmath]w[/ilmath] is not surjective, the point(s) on which [ilmath]\tilde{f} [/ilmath] and [ilmath]\tilde{f}'[/ilmath] disagree on may never actually come up, so it is indeed not-unique if [ilmath]w[/ilmath] isn't surjective.

References

  1. 1.0 1.1 This is my (Alec's) own work